Kemampuan Lilin Aromaterapi Ekstrak Daun Belimbing Wuluh (Averrhoa Bilimbi) Sebagai Pengusir Lalat Rumah (Musca domestica) - Rasjid, Ashari; Haerunnisya, Nur Magfira; Budirman (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2023)
Flies are vectors that can cause disease for humans. The presence of flies greatly interferes with human life. To break the chain of disease transmission from flies, it is necessary to carry out control. For example, the use of natural insecticides from star fruit plants (Averrhoa bilimbi) which has chemical compounds that are toxic to fly vectors. The purpose of this study was to determine the effectiveness of aromatherapy candles of star fruit leaf extract (averrhoa bilimbi) as a house fly repellent (musca domestica). This type of research is experimental research. The samples used in this study were 100 house flies (musca domestica) with an exposure time of 1 hour with an interval of 20 minutes with 3 repetitions and the concentration of extracts used was 30%, 40% and 50%. The results showed that at a concentration of 30% the average total evicted flies were 4 heads with a percentage of 40%, the concentration was 40% of the total average evicted flies as many as 5 heads with a percentage of 50%, and the concentration of 50% of the total average evicted flies were 8 heads with a percentage of 80%. Inferred from the three concentrations used, the most effective concentration in repelling test flies is a concentration of 50%. So it is recommended that people use star fruit leaf wax in repelling flies. Keywords : Aromatherapy Candles, Extract, Star Fruit Leaves Wuluh, House repellents and flies.